AI Chatbot to Improve Students' Vocabulary Mastery - Irmawati; Dzakiah; Fatima (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Artificial Intelligence (AI) Chatbots are computer programs designed to simulate human conversation and offer interactive, personalized learning experiences. This quantitative study investigated the effectiveness of an AI Chatbot (implemented using the website platform https://www.aichatting.net) in improving students' vocabulary mastery at SMP Negeri 01 Dapurang Pasangkayu, Indonesia. The study employed a quasi-experimental design, comparing an experimental class (8B, n = 25) that utilized the AI Chatbot with a control class (8B, n = 25) that employed a conventional teaching method. The intervention was conducted over six sessions across three weeks, from April 26 to May 19, 2025. Students completed pre-tests and post-tests to assess vocabulary mastery. The experimental class mean score increased from 31.60 to 76.00 (gain = 44.40; Cohen’s d = 4.71), while the control class improved from 32.00 to 46.00 (gain = 14.00; Cohen’s d = 1.43). An independent samples t-test on post-test scores revealed a statistically significant difference between the classes, t (48) = 12.42, p < .0001, with a 95% confidence interval of \ [25.27, 34.73]. These results confirm that the AI chatbot had a substantial impact on vocabulary mastery in practice. While the study supports the potential of AI chatbots as effective vocabulary-learning tools in junior high school settings, it also acknowledges the limitations of the quasi-experimental design and recommends further research using randomized controlled trials.